2019
DOI: 10.1111/jphd.12313
|View full text |Cite
|
Sign up to set email alerts
|

Mouth self‐examination as a screening tool for oral potentially malignant disorders among a high‐risk Indigenous population

Abstract: Objectives To evaluate the efficacy of mouth self‐examination (MSE) as a self‐screening tool for detection of oral mucosal lesions among an Indigenous population in Malaysia at high risk for oral premalignant and malignant disorders. Methods Two villages were selected as the sampling frame based on prevalence of tobacco and betel quid chewing habit. Respondents were asked to check their mouth for presence of lesion or abnormalities. Education on oral cancer, including MSE, was provided. Subsequently, responden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 28 publications
1
17
0
Order By: Relevance
“…Many studies reported the lack of general population awareness and knowledge regarding oral cancer 2,9 . In the present, we believe that the diagnosis of only one OSCC and 25 OPMDs from 1.282 screened patients may reflect that the real at-risk population was not reached.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies reported the lack of general population awareness and knowledge regarding oral cancer 2,9 . In the present, we believe that the diagnosis of only one OSCC and 25 OPMDs from 1.282 screened patients may reflect that the real at-risk population was not reached.…”
Section: Discussionmentioning
confidence: 99%
“…Similar results were observed in the study conducted by Ghani et al . [ 7 ] and Elango et al . [ 19 ] The most prevalent lesion recorded in the present study was difficulty in mouth opening.…”
Section: Discussionmentioning
confidence: 99%
“…Utilizing theory, observation, expert opinion, and previous studies,[ 7 27 ] a questionnaire was prepared which was validated before the data collection. The final questionnaire consisted of three subdivisions: sociodemographic details, history of risk factors, and practice of MSE.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Healthcare is expected to become increasingly inadequate over the coming years. If we rely on existing conventional diagnostic technologies, which are subjective and depend on examiner experience, provision of sufficient quality and quantity of these would place further demands on the availability of healthcare 39 .…”
Section: Figure 2 Roc Curve -Sensitivity and Specificity Of Coe In Pmentioning
confidence: 99%